MARKETING STRATEGIES FOR LOCAL MSME PRODUCTS THROUGH THE UTILIZATION OF DIGITAL PLATFORMS IN THE NEW NORMAL ERA - Silvia Ekasari (JOURNAL OF COMMUNITY DEDICATION, 2023)
This study aims to investigate the marketing strategy of local MSME products through the utilization of digital platforms in the new normal era. In the midst of new normal conditions marked by changes in consumer behavior and limited physical interaction, the use of digital platforms is crucial for the survival of MSME businesses. This study uses the literature review method by finding references in accordance with the research context. The results of the research findings show that MSMEs that implement digital marketing strategies effectively usually integrate several platforms such as social media, online marketplaces, and personal websites. Creative and personalized content, the use of SEO, and data analytics prove to be important in increasing interaction and sales. On the other hand, factors such as limited digital knowledge, financial capacity for initial investment, and cybersecurity are major barriers. The study also showed a significant increase in sales and market expansion for MSMEs that managed to overcome these barriers and implement digital strategies well.